New contributions to the genus Bordeta Walker, [1865] from Morotai and Halmahera, Indonesia, with descriptions of a new species and another subspecies (Lepidoptera: Geometridae, Ennominae, Boarmiini, Milioniidi) - Expósito-Hermosa, Andrés (SHILAP Revista de lepidopterología, 2023)
Bordeta sarae Expósito, sp. nov. of Morotai and Bordeta quadriplagiata halmaherae Expósito, ssp. nov. of Halmahera, Indonesia. Illustrations of the adults are included, as well as the genitalia of the males.